Collaborative meta-profile development to harmonise mechanical engineering education in Africa - S. M. Sackey; V. R. Ancha; M. P. Chinyama; C. Awono Onana; R. Danwe; M. M. Megahed; B. Delpouve; S. Chama; N. Mahomed; V. Kayibanda; L. Y. Kabeya Mukeba; A. Müller (Universidad de Deusto, 2014)
This paper describes the contribution of the Tuning Methodology toward harmonisation of undergraduate mechanical engineering programmes in Africa. This methodology is an interactive process in which academics develop high quality curricula and learning standards for students through the identification of generic and subject specific competences in consultation with employers, students, graduates, peers and other stakeholders involved in Mechanical Engineering higher education. The current Tuning process involves academics in 11 universities drawn from across Africa. The aim is to collaboratively contribute to revitalizing and reforming Mechanical Engineering higher education in Africa to make it more responsive to Africa's developmental needs. The results so far show that such a project is not only highly feasible but also holds promise for establishing compatible academic structures and reference standards across Africa, which would facilitate student and staff mobility as well as enhance cooperation not only among African academic institutions, but also between African institutions and those in the rest of the world. Eighteen generic competences and nineteen mechanical engineering-specific competences are developed, analysed and synergised to form a meta-profile that will inform the next phase of the project, which is the actual curriculum development. This activity is part of "Tuning Africa" project, which is funded through European Union-African Union collaboration.